(untitled) (PHRASIS | Rivista di studi fraseologici e paremiologici, 2020)
The aim of this paper is to discuss the compilation of an Online English Collocations Platform, designed to help Brazilian Portuguese as well as other foreign language speakers to learn English. Moreover, we address the role and importance of collocations in foreign language learning, teaching and training. The Platform activities have been firstly developed based on some difficulties Brazilian Portuguese speakers have in learning collocations in English, according to research data results (Orenha-Ottaiano, 2012a, 2012b, 2013; Brito; Orenha-Ottaiano, 2013). The data was obtained from: 1) a Translation Learner Corpus (parallel) made up of texts translated from Portuguese into English by B.A. in Translation undergraduate students, and 2) a Learner Corpus composed of essays written in English by B.A. in English language undergraduate students. In addition to that, other collocations have been added to the Platform, which may also help the target audience develop their collocational competence in English. To build up the Platform activities, the methodology involves the extraction and analysis of collocations from the referred learner corpora (to focus on Brazilian students’ difficulties and needs) as well as the extraction of frequent collocational patterns from EnTenTen15, from the Sketch Engine (Kilgarriff et al., 2004), The Platform is expected to help preand in-service teachers work with the referred phraseologisms in the classroom more effectively and learners use them more accurately and productively with a view to have one more resource to develop collocational competence and fluency in English.